Bidirectional associations between affective empathy and proactive and reactive aggression. Issue 4 (30th March 2020) - Tampke, Elizabeth C.; Fite, Paula J.; Cooley, John L.
Abstract: Preliminary evidence indicates that affective empathy is differentially related to proactive and reactive functions of aggression. However, additional longitudinal research is needed to understand the potential reciprocal nature of these links. The current study examined the bidirectional associations between affective empathy and proactive and reactive aggression over a 6‐month period during middle childhood, with attention to potential gender differences. Data were collected from 294 elementary school children (52% girls; M  = 9.25 years; SD  = 0.944 years) and their homeroom teachers. Affective empathy was assessed using self‐reports, and teachers provided ratings of children's functions of aggression. Data were collected during the fall and spring of one academic year. Overall, results suggest some evidence that affective empathy and functions of aggression are reciprocally linked over time. As predicted, Time 1 empathy was inversely associated with Time 2 proactive aggression and Time 1 reactive aggression was inversely associated with Time 2 empathy. Contrary to expectations, Time 1 proactive aggression was marginally positively associated with Time 2 empathy, and Time 1 empathy was not significantly associated with Time 2 reactive aggression. These prospective links did not differ according to gender. Implications and directions for future research are discussed.